Challenges of Conducting Research With Young Offenders With Traumatic Brain Injury. Issue 6 (November 2018) - O'Rourke, Conall; Templeton, Michelle; Cohen, Miriam H.; Linden, Mark A.
Abstract : The purpose of this commentary is to highlight the challenges encountered when conducting research with young offenders. This is drawn from the first-hand experience of 3 researchers working on separate projects within this environment. Young offenders present as a complex clinical population with high levels of illiteracy, substance abuse, and mental health issues. Significant planning is therefore required before working with this group. Consideration must be given to the heterogeneity of prison populations alongside the potential limitations of datacollection methods, in particular, reliance on self-report. The capacity of young offenders to comprehend and effectively engage with research is also of concern, posing issues of both a practical and ethical nature. The absence of a consistent "research culture" within prison environments poses further practical challenges, potentially also placing significant burden on both researchers and prison resources. The challenges discussed in this article may help inform future studies in the area and emphasize the need for greater critical reflection among researchers conducting work of this type.